A Critical Analysis of the State of Modern Slave in the 21st Century - Mwemezi, Peter (Darul Yasin Al Sys, 2023)
The study critical examines slavery in the modern day with focus on examination of contemporary slavery in Africa. The phenomenon of slavery can be traced from the dawn of time and it banned in the 19th century. However, millions of people are still suffering under what called modern day slavery. The results of this study is basically based on secondary data sources. It is revealed that forced labor, sex slavery, practice of debt bondage and trafficking in human beings, all these are types of modern slavery. This human tragedy has become most effective business in the 21st century, although it is illegal around the world as well recognized as a violation of one’s human being. The impacts of this is tremendous as well contrary to the modern civilized community. The study reveals that modern day slavery in the 21st century compose a complete breaches of fundamental human rights together with a global blackmail to democracy, peace as well sustainable development.